Listening Learning Design by Using Gagne’s Nine Instructional Events to Trigger Student Learning Communication - Muhammad Syihabul Ihsan Al Haqiqy; Huda, Nurul; Halifah, Nur; Al Haqiqy, M. Sirajuddin (Asalibuna, 2024)
There are learning problems when in the field, not a few students are less enthusiastic and lack response when listening learning activities take place. In this case, learning needs to use strategies in delivering material so that learning outcomes can be achieved efficiently. Therefore, the researcher tried to provide a learning design for listening by using the "Nine Instructional Events Gagne" strategy. This study aims to determine how the design of the concept, implementation, and results of learning maharah Istimā' with "Gagne's Nine Instructional Events" to trigger student learning communication. The method used in this research is classroom action research (PTK) with one cycle. with data collection techniques of observation, documentation, and measurement in the form of tests. The results of this study indicate that a listening learning design that leans towards Gagne's nine events can improve students' responses to the listening process. As evidenced by the first cycle stage, the average score of 75.6 was categorized as good. With the results of student scores reaching 75.6%, it can be said to be successful even though the changes are not so significant, it is known that the learning carried out has improved better than before using Gagne's nine events learning strategy. This research implies that it can provide concepts for the world of education, to provide a learning option.